Modeling of behavioral responses for successful selection of easy-to-train rams for semen collection with an artificial vagina - Ambrosi, Claudia Pamela (2018)
The aim of this study was to analyze the reproductive behavioral responses in Australian Merino rams, to identify those related to a faster training for semen collection with an artificial vagina. Eight Australian Merino rams, aged 1.5 years and with no prior sexual experience, were randomly selected from an extensively grazed flock. One immobilized ewe with no hormone stimulation was used for rams to sexually interact and mount. The frequencies of approaching, sniffing, flehmen, pushing, pawing with chin resting, and tongue flicking were recorded during eight training and three post-training assessments periods. In addition, the duration of sniffing and flehmen responses, as well as the time from when the ram started to approach the ewe until the mount with ejaculation (completed mount) were recorded. Descriptive, correlation, and modeling analyses were performed. Amongst the rams, four mounted the ewe and ejaculated for the first time during the training phase, and three mounted and ejaculated for the first time after the training phase. The remaining ram mounted the ewe and ejaculated for the first time during the post-training evaluation in the following year. A great variability in the behavior repertoire was observed among rams. The correlation analysis indicated that the completed mount was associated with the behaviors during the approaching response. The expression of the sniffing response decreased between the training phase and post-training evaluation, while the responses of pushing the ewe and tongue flicking ceased to occur. Pawing the side of the ewe with the chin resting on the back of the ewe and flehmen responses, however, continued between the training and post-training phases. This led to a decrease in the time from when the ram started to approach the ewe until the completed mount. It is concluded that the responses of approaching the ewe, pawing the side of the ewe with chin resting on the ewe, and sniffing of the ewe (the latter occurring only during the training phase) are behavioral indicators that could be used for selection of easy-to-train rams for purposes of semen collection with an artificial vagina.